Indeks Kesesuaian Wisata Pantai Batu Bolong, Canggu, Badung - Dalem Sukmajaya, Anak Agung Ngurah Agung; Dirgayusa, I Gusti Ngurah Putra; Indrawan, Gede Surya (Journal of Marine and Aquatic Sciences; Vol 9 No 2 (2023)DO - 10.24843/jmas.2023.v09.i02.p05, 2023)
The tourism suitability index (TSI) is criteria of resources and the environment to meet the needs of tourism development. The tourism suitability index research was carried out at Batu Bolong Beach, Canggu with the aim of knowing tourism suitability index and tourism area utilization zone for beach recreation activities. Method used field observation by purposive sampling at 4 station points which are divided into a beach length of 640 m. Data retrieval in the form of 10 parameters: water depth, beach type, water current velocity, coastal slope, water base material, beach width, water brightness, dangerous biota, fresh water availability, and coastal land cover. Tourism suitability analysis based on TSI matrix with considering classification of four types categories. The limiting factors at Batu Bolong Beach are the brightness of the waters and the closure of coastal land. The value of tourism suitability for tourism activities in the beach recreation category based on assessment of stations I, II, III, and IV are different, namely 98.80%, 94.04%, 95.23%, and 91.67%. So this indicates that each station in the coastal area can be declared very suitable category for recreational tourism activities. The zones for use of coastal tourism areas include sports, walks, sunbathing, swimming, and surfing. The sunbathing, walking, swimming, and surfing zones can be done at all stations, while the sports zone can be done at stations I and IV. The sacred zone is located in the northern area, stations I and III which are adjacent to station II.